2011
DOI: 10.1017/s0022381610000952
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ Evaluations of the Fulfillment of Election Pledges: Evidence from Ireland

Abstract: The linkage between what parties promise during election campaigns and what governments deliver afterward is central to democratic theory. Research on this linkage concludes that there is a higher level of congruence between campaign promises and government actions than suggested by the conventional wisdom. This study is the first to describe and explain citizens' evaluations of the fulfillment of election pledges in a way that is comparable with political scientists' evaluations. The explanation of variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 36 publications
5
60
0
2
Order By: Relevance
“…Election promises are a central feature of electoral campaigns, yet we lack a detailed understanding of several of the mechanisms that are at play when promises are made, evaluated, and acted upon in a representative democracy. Even though it is common practice for politicians in virtually all democracies to commit to electoral pledges while running for office, it appears to be common wisdom among some voters that these promises are not reliable (Naurin, ; Thomson, ). This is in line with the common assumption made by scholars modeling postelection behavior (Persson & Tabellini, ) that election promises are uninformative about a politician's future behavior (Barro, ; Ferejohn, ).…”
Section: Experimental Designmentioning
confidence: 99%
“…Election promises are a central feature of electoral campaigns, yet we lack a detailed understanding of several of the mechanisms that are at play when promises are made, evaluated, and acted upon in a representative democracy. Even though it is common practice for politicians in virtually all democracies to commit to electoral pledges while running for office, it appears to be common wisdom among some voters that these promises are not reliable (Naurin, ; Thomson, ). This is in line with the common assumption made by scholars modeling postelection behavior (Persson & Tabellini, ) that election promises are uninformative about a politician's future behavior (Barro, ; Ferejohn, ).…”
Section: Experimental Designmentioning
confidence: 99%
“…We do not have measures of whether voters in each election called for the promises that the parties made. We share this lack of possibility to compare voters' specific policy preferences and parties' pledge making with the other election pledge studies (for a discussion see Naurin, 2011;Thomson, 2011). However, we can test whether the observed increase in promises is a consequence of parties resorting to making more pledges in less salient issue areas.…”
Section: Håkansson and Naurinmentioning
confidence: 98%
“…53 (2004) found that 50 per cent of government and 45 per cent of opposition policies were implemented, and Costello and Thomson (2008) report fulfilment rates of 70 per cent (government) and 44 per cent (opposition) for 2002 -2007. What is more, Thomson (2011) found that Irish manifestos affect policymaking much more than many citizens believe. While the electorate's assessments of pledge redemption varied with the actual fulfilment status of the promises, citizens' views were generally too negative.…”
Section: Manifestos In Irelandmentioning
confidence: 99%